2009
DOI: 10.1111/j.1365-3156.2009.02308.x
|View full text |Cite|
|
Sign up to set email alerts
|

The burden of COPD in Africa: a literature review and prospective survey of the availability of spirometry for COPD diagnosis in Africa

Abstract: Summaryobjectives To ascertain the known burden of chronic obstructive pulmonary disease (COPD) in Africa and of spirometry use to indicate the possibility of further unpublished data becoming shortly available.method Literature review. results Screening of 132 articles yielded 22 relevant articles, of which only six used spirometry based data. A total of 106 physicians in 34 countries were contacted and only 23 reported satisfactory use and availability of spirometry.conclusions Current estimates of COPD burd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 18 publications
1
48
0
Order By: Relevance
“…Several authors have reported that the epidemiological evidence on COPD in African region is still very limited and that this has affected the response to its growing burden in the region [16,34,163,164]. We estimated a prevalence of about 11% in 2010, amounting to 29 million COPD cases in the region.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Several authors have reported that the epidemiological evidence on COPD in African region is still very limited and that this has affected the response to its growing burden in the region [16,34,163,164]. We estimated a prevalence of about 11% in 2010, amounting to 29 million COPD cases in the region.…”
Section: Discussionmentioning
confidence: 97%
“…The burden in LMIC has been comparatively high owing to relatively low COPD awareness, challenges with COPD diagnosis and increased exposures to additional risk factors, especially combustion products of biomass fuels [16]. Salvi and colleagues reported that about 3 billion people globally are exposed to smoke from biomass fuel, compared to 1 billion people who smoke tobacco globally [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…37,39 In other surveys, no bronchodilator was administered or spirometry was not available so the diagnosis was made using symptoms such as shortness of breath, cough, and sputum production for more than three months over the previous two years. 12 Only 10 of the 53 countries in Africa have published data on the prevalence of COPD (e.g. selected populations such as factory workers and miners).…”
Section: Prevalence Of Copdmentioning
confidence: 99%
“…11 Data on CRD and related risk factors are scarce or not available for most developing countries, and only few data on morbidity and economic burden exist, particularly in subSaharan Africa. 12 Information on causes of death among adults in sub-Saharan Africa is essentially non-existent because death certificates are often not issued. 8 …”
Section: Introductionmentioning
confidence: 99%